Comparative Performance Analysis of Different Wind Fields in Southern and North-Western Coastal Areas of the Black Sea - ÇAKMAK, RECEP EMRE; AKPINAR, ADEM; VAN VLEDDER, GERBRANT PH. (Mediterranean Marine Science, 2019)
This study determines the qualities of atmospheric wind field data in comparison with wind measurements at five locations along the Black Sea coast. For this purpose, four different wind fields were obtained from three different weather centres (NCEP, NASA, and ECMWF). Three of these are reanalyses winds (Climate Forecast System Reanalysis CFSR, Modern-Era Retrospective-analysis for Research and Applications MERRA, ECMWF reanalyses ERA-Interim) and one is the operational dataset (ECMWF operational). The performance of them was determined using the wind measurements from 2000 to 2014 at five coastal locations along the southern coastline of the Black Sea (Kumköy, Amasra, Sinop, Giresun, Hopa) and from 2006 to 2009 at offshore location (Gloria) off the coast of Romania. Performances of these wind fields were determined based on statistical characteristics (mean, standard deviation and variation coefficient etc.), statistical error analysis for all data and for different wind speed intervals, wind roses and probability distributions. Besides, long-term variations of yearly error values (SI and bias) of wind speeds from wind data sources during 2000 - 2014 were discussed. Finally, it was concluded that the CFSR winds give the best performance at most stations. The ECMWF datasets yield better results along the western side but CFSR wind fields have shown better performance along the eastern side of the Black Sea coast and at Gloria offshore location.